Mongolia : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Joint Staff Advisory Note reviews the Poverty Reduction Strategy Paper Progress Report for Mongolia. Recent economic developments have been broadly favorable. Real GDP growth exceeded 10.5 percent in 2004 and is expected to remain robust, at about 5.5 percent in 2005, with a recovery in livestock production and strong activity in the mining sector serving as the main drivers of growth. Fiscal performance has strengthened markedly, with the overall deficit narrowing to about 2 percent of GDP in 2004-the lowest level since the start of the transition in the early 1990s.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet